Analisis Penentuan C-Organik Pada Sampel Tanah Secara Spektrofotometer UV-Vis - Kamisah, Kamisah; Kartika, Trimin (Indobiosains, 2024)
Research has been carried out to analyze organic C levels in soil samples using a UV-Vis Spectrophotometer. Carbon in soil functions as a food source for microorganisms, which can accelerate decomposition activities and reactions of organic matter in the soil. The aim of determining organic C levels is to determine the amount of organic carbon contained in soil samples, which plays an important role in assessing soil fertility. The analytical method used is UV-Vis spectrophotometry. The analysis results showed that organic C levels in soil samples ranged from 0.15% to 2.27%. Samples with code D have the highest C-organic content, namely 2.27%, while samples with code A have the lowest C-organic content, namely 0.15%. Most organic C levels were detected in the deficiency (low) category. Low levels of organic C in the soil have an impact on plant growth that is less than optimal. To improve the quality and levels of soil organic C, it is recommended to add compost or urea to reach standards that correspond to good soil quality.